2018
DOI: 10.3390/md16070226
|View full text |Cite
|
Sign up to set email alerts
|

Sorbicillinoid-Based Metabolites from a Sponge-Derived Fungus Trichoderma saturnisporum

Abstract: Antibacterial activity assessment and high performance liquid chromatography associated with nuclear magnetic resonance (HPLC/NMR) data revealed that the EtOAc extract of the fermented endophytic fungus Trichoderma saturnisporum DI-IA, obtained from the marine sponge Dictyonella incisa, contained conjugated olefinic metabolites with antibacterial activity. Chemical examination of the fungal strain resulted in the isolation of eight new sorbicillinoid-based compounds, namely saturnispols A–H (1–8). Their struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 41 publications
1
46
0
Order By: Relevance
“…In many other cases, the transition dipole polarization may be inferred from the symmetry properties of the chromophores. For example, an all- trans polyene chain, or a polyenone, has an effective cylindrical symmetry for which the relevant π–π* transitions are necessary polarized along the chain direction; ECM applications are therefore straightforward [ 16 ]. On the contrary, the thiazoline ring lacks any element of axial symmetry, therefore π–π* transitions can be, in principle, oriented in any direction in the plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many other cases, the transition dipole polarization may be inferred from the symmetry properties of the chromophores. For example, an all- trans polyene chain, or a polyenone, has an effective cylindrical symmetry for which the relevant π–π* transitions are necessary polarized along the chain direction; ECM applications are therefore straightforward [ 16 ]. On the contrary, the thiazoline ring lacks any element of axial symmetry, therefore π–π* transitions can be, in principle, oriented in any direction in the plane.…”
Section: Discussionmentioning
confidence: 99%
“…The most important quality of the ECM is its ease of application; it is also very robust, because it is based on a well-established theoretical basis [ 6 , 12 ]. These two facts render the ECM still popular, in the present computational era, to assign the AC of natural products including marine-derived ones, as demonstrated by a few recent references selected from this journal [ 16 , 17 , 18 , 19 , 20 , 21 ]. The method is so useful that when a compound lacks the necessary chromophores, it may be convenient to introduce them covalently or noncovalently to apply the ECM [ 15 , 22 ], rather than resorting to a different approach.…”
Section: Introductionmentioning
confidence: 99%
“…Strains of E. faecalis A4 (VRE) were inhibited at MIC of 1.63 and 12.9 µg/mL, respectively, by only saturnispol F (6) and saturnispol H (8). These may be promising antibiotics for the treatment of Gram-negative bacterial infections [103]. An alkaloid-producing marine sponge (Epipolasis sp)-associated A. candidus KUFA0062 (Thailand) synthesized a previously unreported bis-indolyl benzenoid, candidusin D (2e), and a new hydroxypyrrolidine alkaloid, preussin C (5b), including another known fourteen compounds.…”
Section: Invertebrate-associated Fungi (Sponges Ascidians Crab)mentioning
confidence: 99%
“…Sorbicillinoids were divided into four classes based on their structure [32]: monomeric sorbicillinoids, bisorbicillinoids, trisorbicillinoids, and hybrid sorbicillinoids. In recent years, various potential applications of sorbicillinoids have been exploited, such as antioxidants [33,34], antibiotics [35,36], and anticancer drugs [37,38]. However, research on sorbicillinoids as a PS for the APDT system has not been reported.…”
Section: Introductionmentioning
confidence: 99%